The Changing Landscape of English Teaching - Ester de Jong (Cranmore Publishing, 2020)
The field of TESOL has seen paradigmatic shifts related to how language and language proficiency are conceptualized as well as how we approach teaching English as an additional language (EAL). Embedding the teaching of English within the world of multilingualism is a third shift. Given the importance of multilingualism for the 21st century and a globalized and technology-enhanced world, viewing EAL teaching as integral to becoming bi/multilingual is imperative. Rather than seeing EAL as separate from students' home language practices, this article argues that, even in foreign language contexts, teachers can accelerate English language learning by extending and building on students' entire linguistic repertoire.